Development of PALUMI Media (Economic Flow Board) Based on Flashcards in IPAS Subjects to Improve Learning Outcomes of 5th Grade Students at SD NU Insan Cendekia Ngadiluwih, Kediri Regency - Elha Qorry Aina; Dewi Agus Triani; Erika Puspitasari; Eliyyil Akbar (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Learning media play an important role in helping students understand concepts, thereby improving learning outcomes. Based on observations in the fifth grade at SD NU Insan Cendekia Ngadiluwih, Kediri Regency, students' learning outcomes in the economic activities material of the IPAS subject still need to be improved. Therefore, a media in the form of PALUMI (Economic Flow Board) based on flashcards was developed. This research aims to: (1) develop PALUMI media based on flashcards; (2) analyze the feasibility of PALUMI media based on flashcards; and (3) test the effectiveness of PALUMI media based on flashcards to improve the learning outcomes of fifth-grade students at SD NU Insan Cendekia Ngadiluwih, Kediri Regency. This research uses the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 20 fifth-grade students. Data collection techniques included observation, interviews, documentation, questionnaires, and tests. Data were analyzed qualitatively and quantitatively thru percentage analysis and N-Gain tests. The research results show that: (1) the PALUMI media based on flashcards was successfully developed using the ADDIE model thru five systematic stages; (2) the developed media was declared very feasible based on the validation results of media experts at 96.9%, material expert I at 88.0%, material expert II at 94.0%, question expert at 92.0%, and teacher response at 94.0%. Student responses also showed a very feasible category, with 98% in the small group trial and 99.3% in the large group trial; (3) the PALUMI media based on flashcards proved effective in improving student learning outcomes, as indicated by an N-Gain value of 0.82 with a high category and an N-Gain Percent of 82% with an effective category. Thus, the PALUMI media based on flashcards is very feasible and effective in improving the learning outcomes of fifth-grade students at SD NU Insan Cendekia Ngadiluwih, Kediri Regency.